2013
DOI: 10.2478/s11696-012-0224-5
|View full text |Cite
|
Sign up to set email alerts
|

Aminohydroxylation of divinylcarbinol and its application to the synthesis of bicyclic hydroxypyrrolidine and aminotetrahydrofuran building blocks

Abstract: Dedicated to Professor Štefan Toma on the occasion of his 75th birthdayAminohydroxylation of prochiral divinylcarbinol and subsequent Pd(II)-catalysed oxy-/amidocarbonylation of aminopentenediols is reported. The method was applied to the preparation of useful building blocks for syntheses of cytotoxic jaspines and glycosidase inhibitor DLX-homologues. The key intermediates, tetrahydrofuranolactones (l-arabino-II) and pyrrolidinolactones (l-arabino-IX and l-xylo-IX), were prepared in a short 2-step sequence fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…Scheme 11. Synthesis of (a) benzyl (3aR,6R,6aS)-6-hydroxy-2-oxohexahydro-4H-furo[3,2-b]pyrrole-4-carboxylate (a precursor for the formation of glycosidase inhibitor derivatives)[40] and (b) benzyl (3aR,6S,6aS)-6-hydroxy-2-oxohexahydro-4H-furo[3,2-b]pyrrole-4-carboxylate[41].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Scheme 11. Synthesis of (a) benzyl (3aR,6R,6aS)-6-hydroxy-2-oxohexahydro-4H-furo[3,2-b]pyrrole-4-carboxylate (a precursor for the formation of glycosidase inhibitor derivatives)[40] and (b) benzyl (3aR,6S,6aS)-6-hydroxy-2-oxohexahydro-4H-furo[3,2-b]pyrrole-4-carboxylate[41].…”
mentioning
confidence: 99%
“…Synthesis of 2-oxo-N-phenylhexahydrofuro[3,2-b]pyridine-4(2H)-carboxamide from 1-(4-hydroxyhex-5-en-1-yl)-3-phenylurea [39].Later on, Jäger et al reported the carbonylation of benzyl ((2R,3S)-2,3-dihydroxypent-4-en-1-yl)carbamate (Scheme 11a) as a key step in the synthesis of novel 1,4-iminoglycitol derivatives as potential glycosidase inhibitors[40]. On the other hand, the PdCl 2 -catalyzed carbonylation of benzyl ((2S,3S)-2,3-dihydroxypent-4-en-1-yl)carbamate gave benzyl (3aR,6S,6aS)-6-hydroxy-2-oxohexahydro-4H-furo[3,2-b]pyrrole-4-carboxylate in a 14% yield (Scheme 11b)[41].…”
mentioning
confidence: 99%